2022
DOI: 10.1007/s00167-022-06992-7
|View full text |Cite
|
Sign up to set email alerts
|

Higher pathologic threshold of increased tibial tuberosity–trochlear groove distance should be considered for taller patients

Abstract: PurposeThe aim of this study was to evaluate the correlation between tibial tuberosity–trochlear groove distance (TT–TG) and body height or knee size, and to find height‐related pathologic thresholds of increased TT–TG. MethodsOne‐hundred and fifty‐three patients with recurrent patellar instability and 151 controls were included. The TT–TG was measured on axial computed tomography (CT) images. Femora width and tibial width were selected to represent knee size. The correlation of TT–TG and gender, body height, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…However, as the TT-TG distance represents a bare length measurement of the distance between the TT and trochlear groove, it does not account for any rotational differences in the TT, which also likely affects patellar stability. Several other drawbacks have been identified in the assessment of the TT-TG distance, such as compromised measurements in patients with trochlear dysplasia, dependency on body height and knee size and influence of trochlear groove medialization, tibiofemoral rotation, tibial tubercle lateralisation or femoral version in the measurements [1,12,24,27,28,30,31]. Hence, further measurements for patellofemoral instability have been developed over time to overcome these obstacles [5,17,23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, as the TT-TG distance represents a bare length measurement of the distance between the TT and trochlear groove, it does not account for any rotational differences in the TT, which also likely affects patellar stability. Several other drawbacks have been identified in the assessment of the TT-TG distance, such as compromised measurements in patients with trochlear dysplasia, dependency on body height and knee size and influence of trochlear groove medialization, tibiofemoral rotation, tibial tubercle lateralisation or femoral version in the measurements [1,12,24,27,28,30,31]. Hence, further measurements for patellofemoral instability have been developed over time to overcome these obstacles [5,17,23].…”
Section: Discussionmentioning
confidence: 99%
“…However, the TT-TG distance measurement represents a simple length measurement of the distance between the tibial tuberosity (TT) and the trochlear groove, which does not account for rotational differences in the TT that may potentially impact patellofemoral instability. Furthermore, several studies have shown that the TT-TG distance is influenced by numerous individual factors [1,12,24,27,28,30,31]. Therefore, several parameters have been proposed to overcome these impairments [5,17,23].…”
Section: Introductionmentioning
confidence: 99%
“…The CA is defined as the angle formed by the angle bisector of the trochlear groove angle and the line of the lower pole of the patella (Figure 2b). The tibial tuberosity–trochlear groove distance (TT‐TG) was measured as previously described by Wang et al [21]. The Caton–Deschamps index was used to measure patellar height [24].…”
Section: Methodsmentioning
confidence: 99%
“…Many authors have reported morphological changes in the femoral trochlea and posterior femoral condyle in patients with patellar dislocation [17–20]. Yang et al also reported a correlation between anterior and posterior femoral condyle composite deformity and increased FA in patients with patellar instability [21]. A distal derotational femoral osteotomy does not change the abnormal femoral condyle morphology; only the overall femoral torsional deformity does.…”
Section: Introductionmentioning
confidence: 99%
“…The tibial torsion angle was measured between a tangent line of the posterior margin of the tibial plateau and a line connecting the midpoints of the medial and lateral malleoli [24]. The TT–TG distance was measured as previously described by Wang et al [33].…”
Section: Methodsmentioning
confidence: 99%